Manual de Procedimientos para la Unidad de Biblioteca, del Departamento de Vida Estudiantil y Servicios Académicos (DEVESA) del Instituto Tecnológico de Costa Rica, Sede Regional San Carlos - Soto-Arce, Jaime Leonardo (Instituto Tecnológico de Costa Rica, 2014)
This research aims to develop a Procedures Manual which in order to increase efficiency in the administrative management of the Library, in the Department of Student Life and Academic Services (DEVESA) of the Technological Institute of Costa Rica, San Carlos Regional Campus. The Procedures Manual provides a detailed description of the processes that are developed in this Unit, these procedures were constructed through interviews, using a questionnaire and supporting them with direct observation of the processes. In this aspect of the identification procedure, index, introduction, objective, scope, rules or policies, internal and external documents, information systems, tools, concepts, description, activities, analysis and indicators are established in each procedure. This manual describes the procedures performed in the Areas of Material Acquisition and Registration, Technical Processing of Material, Circulation and borrowing, User Education Services and Reference, Communication and Information and Coordination and Administrative Management.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela Administración de Empresas, 2014
Keywords: Servicios bibliotecarios; Manual de procedimientos